AUDIO JOURNAL: ALIH MEDIA JURNAL ILMIAH DALAM BENTUK AUDIO SEBAGAI ALTERNATIF LITERASI DALAM PEMBELAJARAN ENTREPRENEURSHIP - Reza Ginandha Sakti (Universitas Lambung Mangkurat, 2021)
This article describes the creation and use of audio media containing scientific journal content. Scientific Journal is a form of news or communication that contains scientific works and is published on schedule in electronic and / or printed form. Scientific journal articles is made to provide useful information and knowledge. Currently most of the higher education institutions have Journal products. The problem that occurs is that the community does not take advantage of this scientific article, journalists are dominated by academics. Students who are supposed to cultivate scientific literacy are less interested in reading scientific journals. The low literacy culture is relevant to the instant culture of the younger generation who tend to be less likely to read. The purpose of this research is to provide an alternative literacy by transferring scientific article media from reading media to listening media. Scientific articles according to published entrepreneurial material are recorded with digital sound technical standards, this product prototype in the form of an Audio Journal can be accessed through all Digital Podcast Providers. Through the Audio Journal, students have easy access to scientific articles anywhere and anytime. This research uses qualitative methods and an interdisciplinary approach. Scientific journals are windows to an ever-evolving science, so that ease of access should be an important principle. The result achieved in this study is an alternative media literacy that is easy and fun for students to access, especially in the Entrepreneurship course. Audio Journal can also be used by people with disabilities to be able to access journals using listening media.Keywords: audio journaling, literacy, science